Oil Price and Economic Growth in Small Pacific Island Countries - Evan, Lau; Tiru K., Jayaraman (Scientific Research Publishing, 2011)
Among the 14 Pacific Island countries (PICs), only Papua New Guinea has fossil fuel resources. None of the remaining 13 PICs has any energy sources. Consequently, all the 13 PICs are totally dependent on oil im-ports for their economic activities. Recent surges and volatility in oil prices have had serious economic re-percussions on economic growth. Since PICs have limited foreign exchange earning capacities, as they have very narrow range of exports and are highly dependent on foreign aid, high oil prices in recent months have seriously tested their economic resilience. This paper applies the recently developed panel analysis proce-dures to five major PICs, namely Fiji, Samoa, Solomon islands, Tonga and Vanuatu with a view to assess the impact of oil price on economic growth. The findings are that oil price, economic growth and international reserve are cointegrated. The study findings are that although in the long run there is no long run causality relationship between these variables, in the short run the causality linkage runs from oil prices and interna-tional reserve to economic growth. The paper concludes with a brief discussion on policy options